Steroid therapy in Kimura's disease - M V Archana; K Varadaraj Shenoy; Elizabeth Varkey Cherian; Kishan Shetty (Wolters Kluwer Medknow Publications, 2014)
Kimura's disease is a rare condition and generally presents as non-tender subcutaneous swellings in the head and neck region, primarily seen in young Asian males. We report a case of Kimura's disease, who presented to us with swelling in the head and neck region, histopathological examination confirmed the diagnosis. Investigations showed eosinophilia and raised immunoglobulin E levels. The swelling which recurred after excision subsided following short course of steroid therapy.